1997
DOI: 10.1046/j.1365-2346.1997.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind comparison of alizapride, droperidol and ondansetron in the treatment of post-operative nausea

Abstract: To compare the efficacy in the treatment of post-operative nausea and/or vomiting (PONV), 75 patients undergoing gynaecological procedures under general anaesthesia using N2O/enflurane who suffered from PONV in the first hour after surgery were randomly allocated to three groups containing 25 patients each to receive either alizapride 100 mg, droperidol 1 mg or ondansetron 8 mg (i.v.). Patients expressed the severity of their nausea on a Visual Analogue Scale (VAS) ranging from 0 (none) to 10 (as bad as possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(9 reference statements)
1
8
0
2
Order By: Relevance
“…Our results have shown no statistically significant differences between alizapride and ondansetron. Similar results were found in non laparoscopic gynecological surgeries were higher ondansetron (8 mg) and alizapride (100 mg) doses were used 23 . Alizapride (50 mg, 100 mg and 200 mg) was compared to placebo in preventing nausea and vomiting in ambulatory patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results have shown no statistically significant differences between alizapride and ondansetron. Similar results were found in non laparoscopic gynecological surgeries were higher ondansetron (8 mg) and alizapride (100 mg) doses were used 23 . Alizapride (50 mg, 100 mg and 200 mg) was compared to placebo in preventing nausea and vomiting in ambulatory patients.…”
Section: Discussionsupporting
confidence: 82%
“…Pelos nossos resultados, pudemos observar que não houve diferenças estatisticamente significativas entre a alizaprida e o ondansetron. Resultados similares aos nossos foram observados em cirurgias ginecológicas não laparoscópicas nas quais foram utilizadas doses superiores de ondansetron (8 mg) e de alizaprida (100 mg) 23 . Em pacientes ambulatoriais, comparou-se a alizaprida com o placebo, quanto à efetividade em prevenir náusea e vômi-to.…”
Section: Discussionunclassified
“…The visual analog scale has been used to apply an objective measurement to subjective perceptions. [1][2][3][4][5][6][7][8][9][10] Although the visual analog scale has not been rigorously validated in the measurement for nausea, 2 investigators have demonstrated good correlation with verbal categorical measures of nausea in cancer and postoperative patients and support its use in clinical assessment. 5,6 Psychologists have used the visual analog scale for many years to measure subjective experiences such as mood and affect.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…In the medical literature, it has been applied to the evaluation of a variety of symptoms, including pain, asthma severity, abdominal pain, and nausea. [1][2][3][4][5][6][7][8][9][10] It is simple to administer and is particularly useful for repeated measures in the same individual and for quantitative comparisons between groups of patients.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Durante anos, NVPO foram considerados efeitos inerentes à aplicação de anestésicos ou , bem como diversos agentes farmacoló-gicos como os fenotiazínicos proclorperazina [20][21][22] , prometazina [23][24][25] e perfenazina 26,27 ; os butirofenônicos haloperidol [28][29][30][31] e droperidol 25,[32][33][34][35][36][37][38][39] ; os anti-histamínicos difenidramina (dimenidrato) 40,41 ; hidroxizina 42,43 e ciclizina 4447 ; dentre os anticolinérgicos, a escopolamina 23,4850 ; os benzamídicos como a metoclopramida 33,37,[51][52][53][54][55][56][57] e domperidona 33,37,[58][59][60][61] ; a alizaprida [62][63][64][65] ; os corticosteróides 33,[66]…”
Section: Introductionunclassified